Molecular coupling of a Ca2+-activated K+ channel to L-type Ca2+ channels via alpha-actinin2 - Lu, Ling; Zhang, Qian; Timofeyev, Valeriy; Zhang, Zhao; Young, J. Nilas; Shin, Hee-Sup; Knowlton, Anne A.; Chiamvimonvat, Nipavan (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Cytoskeletal proteins are known to sculpt the structural architecture of cells. However, their role as bridges linking the functional crosstalk of different ion channels is unknown. Here, we demonstrate that a small conductance Ca2+-activated K+ channels (SK2 channel), present in a variety of cells, where they integrate changes in intracellular Ca2+ concentration [Ca-i(2+)] with changes in K+ conductance and membrane potential, associate with L-type Ca2+ channels; Ca(v)1.3 and Ca(v)1.2 through a physical bridge, alpha-actinin2 in cardiac myocytes. SK2 channels do not physically interact with L-type Ca2+ channels, instead, the 2 channels colocalize via their interaction with alpha-actinin2 cytoskeletal protein. The association of SK2 channel with alpha-actinin2 localizes the channel to the entry of external Ca2+ source, which regulate the channel function. Furthermore, we demonstrated that the functions of SK2 channels in atrial myocytes are critically dependent on the normal expression of Cav1.3 Ca2+ channels. Null deletion of Cav1.3 channel results in abnormal function of SK2 channel and prolongation of repolarization and atrial arrhythmias. Our study provides insight into the molecular mechanisms of the coupling of SK2 channel with voltage-gated Ca2+ channel, and represents the first report linking the coupling of 2 different types of ion channels via cytoskeletal proteins.
Keywords: ACTIVATED POTASSIUM CHANNELS; NULL MUTANT MICE; SMALL-CONDUCTANCE; FUNCTIONAL ROLES; ALPHA-ACTININ; CALCIUM-CHANNELS; CALMODULIN; MYOCYTES; CYTOSKELETON; MODULATION